2005
DOI: 10.1080/02699050500110785
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden, time spent caring and health status in the first 12 months following stroke

Abstract: Potentially modifiable factors such as these may be able to be targeted by caregiver training, support and education programmes and outpatient therapy for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
116
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(135 citation statements)
references
References 40 publications
14
116
2
3
Order By: Relevance
“…Family caregivers are at risk for depression, social isolation, declining health, and mortality as a result of providing care, 539 and they experience a considerable burden. 4 Depression prevalence in stroke caregivers has been estimated to range from 30% to 52%, 4,538,540 with higher depression rates in caregivers than in stroke survivors.…”
Section: Family Caregiver Education and Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Family caregivers are at risk for depression, social isolation, declining health, and mortality as a result of providing care, 539 and they experience a considerable burden. 4 Depression prevalence in stroke caregivers has been estimated to range from 30% to 52%, 4,538,540 with higher depression rates in caregivers than in stroke survivors.…”
Section: Family Caregiver Education and Supportmentioning
confidence: 99%
“…543 Because family caregivers of aphasic survivors have been found to experience greater difficulty with tasks and worse life changes than caregivers of nonaphasic survivors, 543 109,111,550 whereas others have reported lower scores. 539 Most stroke caregiver intervention studies have not found significant improvements in general health perceptions, although most used the SF-36, which is considered a more global measure. 109 Even with inconclusive evidence regarding the health status of stroke family caregivers, current practice guidelines recommend that all members of the survivor's interdisciplinary team attend to the health status of family caregivers throughout all phases of rehabilitation.…”
Section: Information On Stroke-related Carementioning
confidence: 99%
“…1 Immediate admission to hospital for treatment and rehabilitation is recommended, however, most patients return home with some residual disability. 2 Substantial reliance and burden is placed on informal caregivers, usually family members, to provide assistance with activities of daily living, including dressing and toileting after hospital discharge, 3 which can aff ect caregivers' physical and psychosocial wellbeing. 4,5 The economic value of the informal care provided is substantial.…”
Section: Introductionmentioning
confidence: 99%
“…7 For example, caregiver stress has been shown to interfere with rehabilitation of the survivor 7 and can result in social isolation, declining health, and increased risk of mortality for the caregivers. 9,10 Depression is especially prevalent in stroke family caregivers, 7,11,12 with some studies reporting higher depression rates in the caregivers than in the survivors for whom they provide care. 11,13 Miller and colleagues 14 made recommendations for family caregiver education and support across inpatient, outpatient, and chronic care settings based on clinical practice guidelines and existing research.…”
mentioning
confidence: 99%